Upaya Meningkatkan Hasil Belajar Siswa Pada Pelajaran Matematika Dengan Menggunakan Pendekatan Realistic Mathematics Education (Rme) Di Kelas II SDN 3 Muara Belida - Natasya Natasya; Fauzi Fadliansyah (Desanta Publisher, 2024)
This research aims to improve mathematics learning outcomes using the Realistic Mathematics Education (RME) approach for class II students at SD Negeri 3 Muara Belida. The RME approach was carried out on class II students at SDN 3 Muara Belida who were the objects of research using the Classroom Action Research (PTK) model. The RME model has proven successful in improving student learning outcomes in Mathematics by making 90% of class II students pass the KKM. In the pre-cycle, only 1 student succeeded in achieving the KKM or 6%, then it increased to 50% in cycle 1 with the number of students who passed the KKM being 6 out of a total of 16 students with an average score of 71, then at the end of cycle II, there were 15 students who succeeded in reaching the KKM with a percentage of 93.75% with an average score of 89.